Self-deception as a technique of neutralisation: an analysis of the subjective account of a white-collar criminal - McGrath, Joe (Crime, law and social change, 2021)
Neutralisation theory suggests that wrongdoers will rationalise their wrongdoing in such a way that allows them to maintain their views of themselves as moral law-abiding people. Though regularly applied since it first emerged as an aspect of differential association theory, it has rarely been extended beyond its original conceptualisation. Moreover, scholars rarely consider the subjective belief systems of criminals or their own accounts of their wrongdoing, when applying this theory. This is particularly true of white-collar criminals where there is a dearth of scholarship analysing how they respond to their own criminality. This article addresses these criticisms by analysing how self-deception may operate as a technique of neutralisation for white-collar criminals, anchoring and applying this extension in a specific case study on white-collar crime, from the subjective perspective of the criminal. It analyses the case of Kareem Serageldin, often considered the only banker jailed in the US for having some role in causing the financial crisis. The Serageldin case is used as a lens to extend and apply neutralisation theory in the field of white-collar crime, exploring how Serageldin distorted the facts of his wrongdoing, deceiving both himself and the court, to minimise his responsibility for his crime.